Analisa Faktor Struktural pada Kesamaan Kesempatan Transportasi untuk Kemudahaan Mengakses Angkutan Umum Bagi Disabilitas - Amini, Lulu Hafsyah; Rachmat, Shanty Yulianti (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
Equality is something that is often a focus in transportation. Equality in the transportation system includes the availability and accessibility of transportation modes for all levels of society. In big cities, it often happens that facilities are available but do not fully meet the needs of all users, including people with disabilities. Difficulty in accessing transportation facilities and infrastructure for people with disabilities eliminates equal opportunities in using public transportation. The city of Bandung is an example of a metropolitan city with 1,814 people with disabilities in 2021 which is trying to increase the accessibility of public transport for all groups of society, including people with disabilities. In addition, with Law No. 8 of 2016 which states that Persons with Disabilities are anyone who experiences physical, intellectual, mental and/or sensory limitations for a long period of time who, in interacting with the environment, may experience obstacles and difficulties in participating fully. and effectively with other citizens based on equal rights. This research was conducted to identify the problems faced by people with disabilities when using city transportation. The research method used is a qualitative method using NVivo software. The analysis method used is thematic analysis. The findings from this research are that there are phenomena in structural factors including bus stops, schedules, public transportation and sidewalks. The challenges that occur with this structural factor are not using bus stops or terminals, long waiting times, public transport conditions that are not disability friendly, sidewalks being converted, and no sidewalks.